A correlational study between serum asymmetric dimethylarginine level and impaired glucose tolerance patients associated with obesity. Issue 7 (7th December 2018) - Huang, Shan; Xu, Yong; Peng, Wen‐Fang; Cheng, Jie; Li, Hui‐Hua; Shen, Li‐Sha; Xia, Li‐Li
Abstract: Asymmetric dimethylarginine (ADMA) plays a vital role in the regulation of insulin sensitivity and has been shown as a potential marker for various disease, including type 2 diabetes mellitus (DM2). However, the correlation between ADMA and impaired glucose tolerance (IGT) and obesity has not been studied. A total of 195 subjects were involved in our study. The characteristics of the subjects in the study cohort were measured and analyzed. We found that the serum ADMA and C‐reactive protein levels were significantly increased in IGT and diabetic patients, whereas the levels of lipoprotein A and adiponectin were decreased, especially in diabetic patients with obesity. The serum ADMA level was positively correlated to a homeostatic model assessment for insulin resistance, and multivariate regression analysis further indicated that ADMA was an independent factor for DM patients with obesity. Our study expands the understanding of the complicated relationship between obesity, insulin resistance, IGT, and ADMA. In addition, we demonstrated that the serum ADMA level could serve as a diagnositic biomarker of the early signs for IGT patients with obesity. Abstract : We found that the serum asymmetric dimethylarginine (ADMA) level was positively correlated to homeostatic model assessment for insulin resistance (HOMA‐IR), and multivariate regression analysis further indicated that ADMA was an independent factor for diabetes mellitus (DM) patients with obesity. Our study expands the understanding of the complicated relationship between obesity, insulin resistance, impaired glucose tolerance (IGT), and ADMA. In addition, we demonstrated that the serum ADMA level could serve as a diagnositic biomarker of the early signs for IGT patients with obesity.